(untitled) (Bangladesh Journal of Pharmacology, 2016)
In order to study the influence of amino acid neurotransmitters secreted by the nerve cells after ketamine treatment, the nerve cells were cultured in vitro to exclude the interference of other factors in vivo and treated with three different doses of ketamine (1, 3 and 5 µg/mL). Then, the concentration of neuronal amino acid neurotransmitters was examined at 0, 15, 30, 45, 60, 90, 120 min after treatment. The trends of each amino acid concentration after ketamine treatment were nearly the same among the different treatment doses. After 15 min of adapting time, ketamine decreased the excitatory amino acid glutamic acid and aspartic acid concentration, and increased the concentration of the inhibitory amino acid glycine. Their concentrations showed a tendency to return approximately to the original level after 120 min.